Prevention of work-related accidents : a different strategy in a changing world of work? (Luxembourg, 2002)
The report is being launched on 22 November at the conference 'Prevention of work-related accidents: a different strategy in a changing world of work?' which forms the closing event of the 2001 European Week for Safety and Health at Work.